Morphology-controllable wrinkled hierarchical structure and its application to superhydrophobic triboelectric nanogenerator. (July 2021) - Ahn, Junseong; Zhao, Zhi-Jun; Choi, Jungrak; Jeong, Yongrok; Hwang, Soonhyoung; Ko, Jiwoo; Gu, Jimin; Jeon, Sohee; Park, Jaeho; Kang, Mingu; Del Orbe, Dionisio V.; Cho, Incheol; et al.
Abstract: Hierarchical structures allow one to improve device performance by exploiting the synergistic effects of micro/nano multiscale components. However, the structural complexity of hierarchical structures places limits on their fabrication and applications. Herein, a novel morphology-controllable wrinkled micro/nano hierarchical structure (WHS) was developed by integrating micropatterns, nanopatterns, and wrinkles on a single substrate to overcome these limitations. Each structure could be individually controlled, which offers unlimited design diversity. The produced WHS was used as a superhydrophobic triboelectric nanogenerator. Compared to a nanogenerator with on a film structure, the WHS-based nanogenerator showed a superior contact angle of 152.5°, which is indicative of high hydrophobicity, and an enhanced (by 608%) triboelectric effect, which was ascribed to the highly rough surface of the WHS. The WHS-based nanogenerator was used to fabricate a self-powered and water-repellent cough detection sensor with an entirely superhydrophobic structure and stable superior sensing performance during repeated water spraying. Graphical Abstract: This study describes a novel fabrication method of hierarchical structures, which can integrate micropatterns, nanopatterns, and wrinkles on a single substrate. This method allows one to independently control three different structures and thus fabricate the wrinkled micro/nano hierarchical structures (WHS). The WHS is utilized as a self-powered and water-repellent cough detection sensor that maintains detection performance during repeated water spraying. ga1 Highlights: A novel fabrication method for wrinkled hierarchical structures (WHSs) is described. Micropatterns, nanopatterns, and wrinkles can be integrated on a single substrate. WHSs is utilized as a superhydrophobic triboelectric nanogenerator (S-TENG). We demonstrate S-TENG as self-powered and water-repellent cough detection sensors. The sensor maintains superior detection performance during repeated water spraying.